The Lexicon of Kaliuda to Improve the Student’s Descriptive Writing Text - Tatu Rija; Ida bagus Putra Yadnya; Putu Sutama (RETORIKA: Jurnal Ilmu Bahasa, 2019)
This study aims to determine the kinds of lexicon discovered in kaliuda that has several motive so the students can learn and finding out the lexicon that improve students’ writing descriptive text. Because by studying and multiplying the vocabulary the students will be easier to write the descriptive text. Students’ ability to write descriptive text relates to mastery of vocabulary. Mastery vocabulary as a basic for mastering language skills that can increase students’ ability to express and writing as productive skill. The method of data collection in this study were obtained by observation consist of several technic, observe the students’ learning process then continued by data arranging suitable with lexicon that contained in Kaliuda as a learning media. The data obtained was conveyed by qualitative method. The students’ writing skill can increase of lexicon was found from kaliuda. The result of this study show that kaliuda has many lexicon inside. At the beginning the students asked to find out the various motive to described it. Based on the students’ descriptions of the kaliuda is able to make the students improve their writing descriptive text skill. By using kaliuda motive the students directly imagine what they will learn such as the lexicon, language use, and etc. Kaliuda as description quite interesting and good to enrich their vocabularies in order to improve the capability of writing descriptive text.